The perception of tofu entrepreneurs on the factors affecting the decline of the tofu industry in Kuningan Regency - Sugianto, Ahmad; Dahlan, Dahlan; Rusmana, Endang; Aisyah, Siti; Suciaty, Tety (International Journal Labs, 2025)
This study aims to understand tofu entrepreneurs' perceptions of the factors affecting the decline of the tofus industry both simultaneously and partially in Kuningan Regency. The study employs descriptive quantitative methods through a survey approach, aiming to explain and summarize various conditions and situations while revealing problems or facts in more depth. This study also utilizes measurements and analyses to explore the views of tofo entrepreneurs regarding the elements that contribute to the decline in the number of industries. The results indicate that the entrepreneurs' perceived factors regarding capital, raw materials, labor, marketing, and training simultaneously have a significant effect on the decline, with a p-value of 0.049 0.05. In contrast, the capital factor does not have an impact on industry decline, while the marketing factor partially influences industry decline. In addition, the effect of reactivating tempeh-tofu cooperatives (Kopti) on operational efficiency and profitability is not significant. The findings provide practical implications for policymakers and entrepreneurs to address industry challenges. These avenues could provide valuable insights and actionable strategies that could be applied locally.